PHRÓNESIS EN FEDÓN Y PROTRÉPTICO (Stylos, 2021)
Beyond the open discussion about whether there is a Platonic or Academic period in Aristotle and, even, whether the Protrepticus can be included within it, in this paper we intend to highlight the interesting point –although not so often examined– of the narrow relationship between the treatment of phrónesis in the Phaedo and in the Protrepticus. In order to do so, we will start from the analysis of the concept of phrónesis in the Phaedo, where we find a double approach to the term that represents both the most desirable end to be achieved as well as that practical wisdom that allows us to adequately evaluate certain situations in life. Next, we will return to this double platonic aspect of phrónesis as a means and as an end of the good life in some selected fragments of the Protrepticus to show how Aristotle adheres to the Platonic anthropological conception in terms of a guiding soul that subdues the body and whose most excellent function must be the center or télos of human life. We find that phrónesis, in addition to allowing men to philosophize and achieve contemplation and knowledge, also exhibits a practical dimension as the foundation of the proper use of the body to live in the best possible way.
Keywords: Phaedo – Protreptic – Phrónesis – Philosophy.